THE USE OF ROLE PLAY IN TEACHING SPEAKING - Purnamawati, Solliyah; ., Sofian; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract :This research purpose is to investigate the effect size of the use of role play in teaching speaking at the eighth grade students in SMPN 12 Pontianak. The total number of sample in this study was 34 students. The method that is used in this research is pre-experimental method that applies pre-test and post-test to measure the effect (ES) size of the treatment. The instruments of this research are pre-test and post-test. Pre-test is applied before the treatment is given. Meanwhile post-test is applied after the treatment given. The different score of pre-test and post-test are respectively 50.58 and 64.41. The result show that the effect size of the use of role play in teaching is high because the Effect Size (ES) is > 0.5. Based on the mentioned results above, it can be concluded that teaching students to speak in English through role play was successful to be implemented. In other words, role play technique helped the teacher to teach her students to speak in English and encourage students to speak up in the classroom. Keywords: Teaching, Speaking, Role Play. Abstrak : Penelitian ini bertujuan untuk mengetahui besaran pengaruh penggunaan role play dalam pembelajaran berbicara pada siswa kelas 8 SMPN 12 Pontianak. Jumlah sampel dalam penelitian ini adalah 34 siswa. Metode penelitian yang digunakan adalah pre-experimen yang menerapkan pre-test dan post-test untuk mengukur besaran pengaruh dari treatment. Instrument dalam penelitian ini merupakan pretest dan posttest. Pretest dilakukan sebelum pemberian treatment. Sementara itu posttest diberikan setelah pemberian treatment. Perbedaan angkaa ntara pretest dan posttest berturut – turut yaitu 50.58 dan 64.41. Hasil ini menunjukkan bahwa pengaruh penggunaan role play dalam pembelajaran tergolong tinggikarena ES > 0.5.Berdasarkan hasil yang disebutkan sebelumnya, dapat disimpulkan bahwa membelajarkan siswa untuk berbicara bahasa inggris menggunakan role play berhasil dilakukan. Dengan kata lain, teknik role play membantu guru dalam mengajar bahasa inggris dan mendorong siswa untuk berani berbicara di dalam kelas. Kata Kunci :Pembelajaran, Berbicara, RolePlay.